Complete electroweak O (N2c) two-loop contributions to the Higgs boson masses in the MSSM and aspects of two-loop renormalisation - Bahl, Henning; Meuser, Daniel; Weiglein, Georg (The European physical journal. C, Particles and fields, 2024)
Results for the full electroweak two-loop contributions of $$\mathcal {O}\left( N_c^2\right) $$, where $$N_c$$is the colour factor, to the Higgs-boson masses in the MSSM are obtained using a Feynman-diagrammatic approach including the full dependence on the external momentum. These corrections are expected to constitute the dominant part of the two-loop corrections that were still missing up to now. As a consequence of working at $$\mathcal {O}\left( N_c^2\right) $$, the relevant two-loop self-energies decompose into products of one-loop integrals, giving rise to a transparent analytical structure of the self-energies. We compare different renormalisation schemes for $$\tan (β )$$, the ratio of the vacuum expectation values of the two Higgs doublets, and demonstrate under which conditions different renormalisation schemes can be related to each other via a simple reparametrisation. We explicitly show that this is in general not possible for mixed renormalisation schemes due to the presence of evanescent terms. In our numerical analysis, the new corrections are compared with already known two-loop contributions and the experimental uncertainty of the mass of the observed Higgs boson. While smaller than the already known two-loop corrections, the new terms are typically larger in size than the experimental uncertainty. This underlines the relevance of the so-far unknown electroweak two-loop contributions.